Multisite reliability and repeatability of an advanced brain MRI protocol. Issue 3 (16th January 2019) - Schwartz, Daniel L.; Tagge, Ian; Powers, Katherine; Ahn, Sinyeob; Bakshi, Rohit; Calabresi, Peter A.; Todd Constable, R.; Grinstead, John; Henry, Roland G.; Nair, Govind; Papinutto, Nico; Pelletier, Daniel; et al.
Abstract : Background: MRI is the imaging modality of choice for diagnosis and intervention assessment in neurological disease. Its full potential has not been realized due in part to challenges in harmonizing advanced techniques across multiple sites. Purpose: To develop a method for the assessment of reliability and repeatability of advanced multisite‐multisession neuroimaging studies and specifically to assess the reliability of an advanced MRI protocol, including multiband fMRI and diffusion tensor MRI, in a multisite setting. Study Type: Prospective. Population: Twice repeated measurement of a single subject with stable relapsing‐remitting multiple sclerosis (MS) at seven institutions. Field Strength/Sequence: A 3 T MRI protocol included higher spatial resolution anatomical scans, a variable flip‐angle longitudinal relaxation rate constant (R1 ≡ 1/T1 ) measurement, quantitative magnetization transfer imaging, diffusion tensor imaging, and a resting‐state fMRI (rsFMRI) series. Assessment: Multiple methods of assessing intrasite repeatability and intersite reliability were evaluated for imaging metrics derived from each sequence. Statistical Tests: Student's t ‐test, Pearson's r, and intraclass correlation coefficient (ICC) (2, 1) were employed to assess repeatability and reliability. Two new statistical metrics are introduced that frame reliability and repeatability in the respective units of the measurements themselves. Results: Intrasite repeatability was excellent for quantitative R1, magnetization transfer ratio (MTR), and diffusion‐weighted imaging (DWI) based metrics ( r > 0.95). rsFMRI metrics were less repeatable ( r = 0.8). Intersite reliability was excellent for R1, MTR, and DWI (ICC >0.9), and moderate for rsFMRI metrics (ICC∼0.4). Data Conclusion: From most reliable to least, using a new reliability metric introduced here, MTR > R1 > DWI > rsFMRI; for repeatability, MTR > DWI > R1 > rsFMRI. A graphical method for at‐a‐glance assessment of reliability and repeatability, effect sizes, and outlier identification in multisite‐multisession neuroimaging studies is introduced. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:878–888.